Revisiting the Law of Occupation - Cuyckens, Hanne (Nova et Vetera Iuris Gentium, 2017)
In Revisiting the Law of Occupation, Hanne Cuyckens assesses the crucial challenges faced by the law of occupation and considers whether the law of occupation remains adequate to address the current situations of occupation.